The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4236/as.2013.45b010
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of microcystins in water and economic fish in Phayao Lake, and fish ponds along the Ing River tributary in Chiang Rai, Thailand

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When season changes combine with other environmental factors, harmful cyan blooms occur. In Thailand, MC accumulation was found in prawn farms [ 89 , 90 ], fish ponds [ 90 , 91 , 92 ], and recreational reservoirs [ 93 , 94 ], especially in the temperate region of the country with high N and P concentrations. In contrast, the reports of STX from Thailand were associated with only freshwater puffers [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…When season changes combine with other environmental factors, harmful cyan blooms occur. In Thailand, MC accumulation was found in prawn farms [ 89 , 90 ], fish ponds [ 90 , 91 , 92 ], and recreational reservoirs [ 93 , 94 ], especially in the temperate region of the country with high N and P concentrations. In contrast, the reports of STX from Thailand were associated with only freshwater puffers [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microcystins have also been detected in wild and commercially-raised marine and estuarine mussels ( Mytilus trossulus ) from Puget Sound, Washington, D.C., U.S.; Nile tilpaia ( Oreochromis nitoticus ) from Chian Rai, Thailand; and other aquatic foods intended for human consumption [ 26 , 27 , 28 ]. Routine seawater and aquatic animal monitoring in areas where cyanotoxins have been found could provide early that warning that animal and human shellfish consumers could be at risk.…”
Section: Example Animal Sentinel Systems and Eventsmentioning
confidence: 99%
“…Recent research demonstrated that microcystins can accumulate in freshwater fish. For example, microcystins were detected in both fresh water samples and fish in aquaculture ponds in Thailand [ 26 ]. In the mid-2000s, the Nature Conservancy began restoring the Williamson River Delta Preserve in Oregon, USA with the goal of regenerating habitats essential for the survival of the endangered Lost River sucker ( Deltistes luxatus ), and short-nose sucker ( Chasmistes brevirostris ) [ 45 ].…”
Section: Example Animal Sentinel Systems and Eventsmentioning
confidence: 99%
“…Livestock effluent from the basin and sewage discharges from the city is likely the major pollution sources. These significant sources of nutrients, especially nitrogen and phosphorus, contribute to the eutrophication of the lake [2]. Eutrophication leads to algal blooms and subsequently to taste and odor compounds, geosmin and 2-methylisoborneol (MIB) production, reducing the application of the lake water for drinking and contaminating aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication leads to algal blooms and subsequently to taste and odor compounds, geosmin and 2-methylisoborneol (MIB) production, reducing the application of the lake water for drinking and contaminating aquatic animals. Moreover, hepatotoxin microcystin formation in Phayao Lake was also implicated with algal blooms [2].…”
Section: Introductionmentioning
confidence: 99%